Studi Potensi Pengembangan Pembangkit Listrik Hybrid Genset-PV di Wilayah Pesisir Kabupaten Malang - Divac Nabiel Akbar; Binar Surya Gumilang; Afidah Zuroida (Politeknik Negeri Malang, 2023)
The need for electrical energy in a region is increasing along with the growth of the population. Sources of electrical energy derived from fossils will run out over time because this energy is non-renewable. Thus, renewable sources of electrical energy must be developed and become a very urgent need for the community, including in the southern coastal area of ​​Malang Regency, East Java. The location has sufficient solar radiation potential and can be used to generate electrical energy. The development of renewable energy supports the self-sufficiency of the community in fulfilling electricity by utilizing the resources around them. This paper aims to examine the opportunities for developing hybrid power plants (electric generator sets and solar panels) in the southern coastal area of ​​Malang Regency using the HOMER software simulation. The results of the study concluded that generation using a hybrid system, with a COE value of IDR 6,972, an NPC value of IDR 615 (million) and a CO2 emission value of 5,992 kg per year is the recommended system configuration. The results of this study were then taken into consideration in designing a power generation system in the south coast region of Malang Regency.